Inner Prosociality, Hope, Emotional Autonomy, and Subjective Well-Being in Adolescents: A Serial Mediation Model - Eryilmaz, Ali; Kurtulus, Hacer Yildirim; Yildirim, Murat (SAGE PUBLICATIONS INC, 2025)
Determining the mechanisms underlying the relationships between emotional autonomy and subjective well-being is necessary for understanding the psychological functioning of adolescents. The current study examined inner prosociality and hope as serial mediators in the relationships from emotional autonomy to subjective well-being. Using convenience sampling, a total of 355 adolescents (Mage = 14.23 +/- 0.54, 50.4% boys), who were continuing their education in a public secondary school, completed the Emotional Autonomy Scale, Adolescent Prosociality Scale, Children's Hope Scale, and Measurement of Subjective Well-Being. The results indicated direct effects from higher emotional autonomy to greater subjective well-being. Also, there was a significant indirect effect from higher emotional autonomy to greater subjective well-being through higher inner prosociality and hope. These findings may inform the development of interventions, indicating that the cultivation of psychosocial resources like inner prosociality and hope may help improve the subjective well-being of adolescents.
Keywords: adolescents; emotional autonomy; hope; inner prosociality; serial mediation model; subjective well-being; PSYCHOLOGICAL NEED-SATISFACTION; CHARACTER STRENGTHS; NEGATIVE AFFECT; CHILDRENS HOPE; MOTIVATION; BEHAVIOR; ASSOCIATIONS; VALIDATION; INDICATORS; SUPPORT; Social Issues; Social Sciences - Other Topics; Sociology